Consumer groups as grassroots social innovation niches. Issue 3 (4th March 2019) - Signori, Silvana; Forno, Francesca
Abstract : Purpose: The purpose of this paper is to draw on the theoretical framework based on grassroots social innovation niches to analyse how and to what extent participation in consumer groups helps to foster food-related sustainability changes (both at individual, niche and potentially regime levels). Design/methodology/approach: The data have been collected via two online questionnaires: 204 consumer groups (named GAS, from the acronym of Gruppi di Acquisto Solidale) and 1, 658 families belonging to the same groups participated in the research. Findings: The findings reveal that participation in GAS not only makes individuals more responsible towards their consumption choices and lifestyles, but also makes consumers more willing to collaborate with others, more interested in politics (especially local politics) and increases their sense of social effectiveness. Social implications: The paper shows how collective consumption can represent a way to increase and foster sustainable behaviours, with the potential to modify socio-economic regimes. Interesting implications are advanced on the relationship between consumers and mainly local and small-scale food producers and on local public governments' policies. Originality/value: Due to the very high number of respondents, this research represents a unique opportunity to observe a phenomenon which is difficult to study with surveys and questionnaires because of its informal nature. Understanding the mechanisms and processes that give rise and sustain such forms of collective action is highly relevant for finding ways to promote grassroots initiatives and community actions, which are an often neglected area of system-changing innovation towards sustainability.